NAALADL2-AS2 functions as a competing endogenous RNA to regulate apoptosis and drug resistance in DLBCL - Xiaoli Xu; Juan Liu; Cheng Fang; Xu Deng; Danxia Zhu; Jingting Jiang; Changping Wu (Cancer Biology & Therapy)
To explore role of NAALADL2-AS2 as ceRNA in DLBCL. Fluorescence in situ hybridization was used to determine location of NAALADL2-AS2 in cells and to verify its expression in DLBCL tissues. The miRNAs interacting with NAALADL2-AS2 and related regulatory genes were identified by small interfering RNA (siRNA) assay, luciferase reporter assay, fluorescent quantitative polymerase chain reaction, western blotting. DLBCL cells transfected with NAALADL2-AS2 siRNA or control siRNA were treated with doxorubicin, rituximab at different concentrations alone or in combination. The growth curves, drug sensitivity changes of cells before and after transfection were detected by MTT assay, ATP-TCA drug sensitivity test. Cell proliferation was detected by BrdU cell proliferation assay, and apoptosis was detected by Annexin V-fluorescein isothiocyanate/propidium iodide staining. The effects and mechanisms of NAALADL2-AS2 on proliferation, apoptosis, drug resistance of DLBCL cells were studied at cellular level. We confirmed expression of NAALADL2-AS2 in both cytoplasm and nuclei of DLBCL cells. Additionally, we observed elevated levels of NAALADL2-AS2 in DLBCL tissues. We discovered that NAALADL2-AS2 functions as ceRNA to inhibit expression of miR-34a, miR-125a, whereas overexpression of NAALADL2-AS2 indirectly upregulates expression of BCL-2. Interfering with NAALADL2-AS2 promoted apoptosis in DLBCL cells, resulting in approximately a 40% increase in sensitivity to doxorubicin and rituximab. In vivo experiments further confirmed that targeting NAALADL2-AS2 effectively suppressed tumor growth, leading to upregulation of miR-34a and miR-125a, downregulation of BCL-2, and enhanced apoptosis in DLBCL cells, which significantly improved their sensitivity to doxorubicin and rituximab by approximately 50%. These results indicate that NAALADL2-AS2/miR-34a, miR-125a/BCL-2 networks hold promise as therapeutic targets for treatment of DLBCL.